Estado situacional de la fabricación, comercialización de crisnejas de hojas de irapay (Lepidocaryum gracile Martius) en el caserío Cahuide, San Juan, Loreto, Perú. 2023 - Ruiz Sanjinez, Brayan Esthilinguer (2024)
The present study has been developed in Cahuide hamlet, located on IquitosNauta km 57 road, with the purpose of knowing the current state of the use of the species (Lepidocaryum gracile Martius Irapay) in forests surrounding the Cahuide Hamlet. From the obtained results, it is clear that the consumption of the Irapay species has decreased considerably compared to previous years; there is no technique for sustained silvicultural management of the species, which places its perpetuation at risk extraction of Irapay leaves, is in Nanay River basin, this being a task that takes between 8 to 10 days. There are four people dedicated to the extraction of Irapay leaves from the Cahuide hamlet. The cost of the bones strongly influences the manufacturing costs of the crisnejas, reaching 45.92% of the total cost of the species. It is estimated that the extraction of 2,560,000 leaves of the Irapay species implies the use of 853,333 plants of the species. With the production of leaves, 42,666 crisnejas are made, the manufacturing cost of which is S/2.17/crisneja and the sale price is S/.3.00/crisneja; the monthly profit/producer is S/.728.87.